PRACTICAL ASPECT OF NUTRITIONAL SUPPORT FOR WOUND-HEALING PATIENTS : A COMPREHENSIVE SYSTEMATIC REVIEW - L Pahlepi, Atep; Wahyudy Ladala, Evan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The skin is the largest organ system whose primary function is to serve as a barrier to protect the body against foreign microbes and noxious substances. Skin integrity and function require macro and micronutrients for cell turnover to maintain homeostasis, and support new growth, and repair, especially in the event of injury or decreased integrity. Wound healing is an important focus of care across all settings, not limited to any particular condition or age group. Achieving optimal healing requires an understanding of nutritional requirements, and these need to be adapted to the setting and incorporated into a care plan. The aim: The aim of this study to show about practical aspect of nutritional support for wound healing patients. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed databasethe results of our search get 40 articles, whereas the results of our search on SagePub get 448 articles, on Google Scholar 4060 articles. Records remove before screening are 3376, so we get 1172 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Nutrition is influential in wound healing, and some key nutrients extend their benefits to aesthetic outcomes. Several studies have shown associations between nutritional deficits and suboptimal wound healing outcomes. However, the current corpus of evidence remains rather generalized.